Analisis Wacana Piranti Kohesi Gramatikal Substitusi dalam Debat Capres JILID V 2024 - Salammah, Shelly Ika Nur; Ibrahim, Yusuf; Sumarlam, Sumarlam (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
The focus of this research is the discourse of the fifth presidential debate of the Republic of Indonesia 2024. This research aims to describe the Subsitution markers and Subsitution functions of nouns, verbs and clauses that are substituted in the oral discourse of the fifth presidential debate. Furthermore, what functions are obtained as a result of categorical grammatical substitution to support the connection and cohesion between lingual units in the speech of the vision and mission of the presidential candidates. The data source in this research is oral discourse transcribed in the fifth debate of the 2024 presidential candidates. This research is descriptive in nature with data in the form of utterances or conversations in which there is the use of nominal, verbal, and clausal substitution. The data collection in this research uses the listening method and note-taking technique. The results of this study show that there are several variations of substitution found, in the form of; noun - noun, noun phrase - noun, noun phrase - noun phrase, verbal phrase - noun phrase, clause - noun. Abstrak Fokus dalam penelitian ini adalah wacana debat calon presiden 2024 JILID V. Penelitian ini bertujuan untuk mendeskripsikan penanda substitusi dan fungsi substitusi bentuk kata benda, bentuk kata kerja dan klausa seperti apa yang mengalami substitusi dalam wacana lisan tuturan visi dan misi debat calon presiden jilid ke V selanjutnya fungsi apa sajakkah yang diperoleh sebagai akibat dari substitusi gramatikal berkategori guna mendukung keterkaitan dan kepaduan antar satuan lingual dalam tuturan visi dan misi capres. Sumber data berupa wacana tertulis dalam wacana debat calon presiden 2024 jilid v, Penelitian ini bersifat deskriptif dengan data berupa tuturan atau percakapan yang didalamnya terdapat penggunaan substitusi nominal, verbal, dan klausal Data penelitian ini adalah aspek penanda gramatikal berupa substitusi, Pengumpulan data dalam penelitian ini menggunakan metode simak dan teknik catat setelah data ditemukan, kemudian di catat. Menggunakan teknik catat. Metode catat yakni mentranskripsikan bahasa lisan ke dalam bahasa tulis menggunakan transkripsi ortografis sesuai ejaan bahasa Indonesia yang berlaku.